Education specializations of graduates at public and private universities in Greater Poland region - Mrozińska, Agnieszka (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The creation of knowledge-based economy and cooperation in the conditions of globalization and economic integration led to changes in the labour market, which in turn led to changes in the situation of higher education in Poland. Adjusting teaching offer of Polish universities to demands of employers put on their future employees represents an embodiment of educational aspirations of future employees. The aim of this paper is to compare the processes of change which take place in the structure of fields of study at universities with changes visible on the labour market in Poznań and Greater Poland region. The study points the changes that occurred in the structure of specializations chosen by students, and in the structure of a functioning of labour market, and then focuses on the analysis of the intensity, speed and stability of the process of adaptation of these structures in 2008-2014
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 476, s. 138-147
Keywords: graduate; higher education; the process of adaptation; Greater Poland region; absolwent; studia wyższe; proces adaptacji; Wielkopolska